INDEPENDENT PAIRS IN FREE BURNSIDE GROUPS - Pahlevanyan, A. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
In this work we prove that for an arbitrary odd n≥ 1003 there exist two words u( x, y), v (x, y), almost every images of which in free Burnside group B (m, n) are independent.